The Relationship between Religion and Power between the Safavid and Mughal Dynasties in Islamic Politics - Mita Tamaminni’mah; Irfan Musonif; Kholid Mawardi (Penerbit Hellow Pustaka, 2026)
The Safavid and Mughal dynasties were two major Islamic powers that played important roles in shaping the political, religious, and cultural development of the Islamic world during the medieval period. However, previous studies have generally discussed both dynasties separately and predominantly through descriptive historical approaches. This study aims to analyze the relationship between religion and power in the Safavid and Mughal dynasties from the perspective of Islamic politics. This research employed a qualitative approach through library research. The data sources consisted of scientific articles, books, and relevant academic literature published between 2020 and 2025. Data were collected through documentation techniques and analyzed using thematic analysis to identify patterns of religious legitimacy, political authority, and social integration within both dynasties. The findings reveal that the Safavid dynasty constructed political legitimacy through the institutionalization of Shi‘a ideology as the official state doctrine, making religion an instrument of political consolidation and identity formation. Meanwhile, the Mughal dynasty developed a more accommodative and inclusive political model by emphasizing tolerance, cultural acculturation, and social integration in a multicultural society. The study also shows that religion functioned not only as a spiritual system but also as a political instrument in shaping state authority and social order. Furthermore, differences in the relationship between religion and power in both dynasties were strongly influenced by their respective social and cultural contexts. In conclusion, the relationship between religion and power in Islamic political history was dynamic and contextual, reflecting different models of political legitimacy and governance within Islamic civilization.